2012
DOI: 10.1002/mrm.24581
|View full text |Cite
|
Sign up to set email alerts
|

R1 and R2* changes in the human placenta in response to maternal oxygen challenge

Abstract: The results demonstrate the feasibility of non-invasive investigation of placental oxygenation using MRI and the sensitivity of R1 oxygen-enhanced MRI to gestational age. The techniques have the potential to provide unique noninvasive biomarkers in compromised pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 37 publications
5
89
1
Order By: Relevance
“…The DR 1 data were then acquired using a protocol previously described for placental imaging. 13 A baseline T 1 map was acquired under air-breathing to calibrate the sequence monitoring T 1 changes against time. Data for this were acquired using an Inversion Recovery-Turbo Spin-Echo (IR-TSE) sequence with four inversion times (TIs) (60, 300, 1100, 2000 ms) and an acquisition without an inversion pulse to provide a measurement of fully relaxed signal.…”
Section: Fetal Brain and Placentamentioning
confidence: 99%
See 2 more Smart Citations
“…The DR 1 data were then acquired using a protocol previously described for placental imaging. 13 A baseline T 1 map was acquired under air-breathing to calibrate the sequence monitoring T 1 changes against time. Data for this were acquired using an Inversion Recovery-Turbo Spin-Echo (IR-TSE) sequence with four inversion times (TIs) (60, 300, 1100, 2000 ms) and an acquisition without an inversion pulse to provide a measurement of fully relaxed signal.…”
Section: Fetal Brain and Placentamentioning
confidence: 99%
“…13 R 1 values were then generated for each time point on a voxel-by-voxel basis inside the ROI. Median R 1 over the ROI was calculated for each time point.…”
Section: Adult Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations have shown that molecular oxygen when inhaled and dissolved in tissue fluid or blood plasma, can alter T 1 values in the tissue due to its paramagnetic characteristics 3,5 . Similarly, alterations of T 2 * values can be observed in the blood due to the magnetic susceptibility differences between oxy-and deoxyhemoglobin 3 . Tumor hypoxia is associated with radiation resistance.…”
Section: Conclusion: Oe-mri Is a Non-invasive Imaging Modality Thatmentioning
confidence: 99%
“…Innovation/Impact: Oxygenation in tissue has been shown to influence MR physical parameters such as the intrinsic longitudinal relaxation time (T 1 ) and the apparent transverse relaxation time (T 2 *) [1][2][3][4][5] . Investigations have shown that molecular oxygen when inhaled and dissolved in tissue fluid or blood plasma, can alter T 1 values in the tissue due to its paramagnetic characteristics 3,5 .…”
Section: Conclusion: Oe-mri Is a Non-invasive Imaging Modality Thatmentioning
confidence: 99%